B) -2x - 3y2 + 1 or 1 - 3y2 - 2x (rearrange)
Step-by-step:
add (-9) & (+10) to get (+1) : (-9+10 = 1)
= -4x + y2 + 1 - x + 3x - 4y2
combine (-4x) & (-x) to get (-5x) : (-4x+ (-x) = -4x-x = -5x)
= -5x + y2 + 1 + 3x - 4y2
combine (-5x) & (3x) to get (-2x) : (-5x + 3x = -2x)
= -2x + y2 + 1 - 4y2
combine (y2) & (-4y2) to get (-3y2) : (y2 + (-4y2)) = y2 - 4y2 = -3y2)
= -2x - 3y2 + 1 Or 1 - 3y2 - 2x (rearrange)
---
D) -4xy + 4y2 - y - 10 or -10 - 4xy - 4y2 (rearrange)
Step-by-step:
subtract 20 from 0 to get −20 (0-20 = -20)
= −20 − 5xy + 4y2 + 10 − y + xy
add (-20) & (10) to get (-10) : (-20+10 = -10)
= -10 -5xy + 4y2 - y + xy
combine (-5xy) & (xy) to get (-4xy) : (-5xy + xy = -4xy)
= -10 - 4xy + y2 - y or (-4xy + 4y2 - y - 10) (rearrange)